GERMAS TULIN: Gerakan Masyarakat untuk Membantu Ibu Bersalin - Normukhlisa, Normukhlisa; Haryono, Ika Avrilina; Nurliani, Siti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The community movement to assist childbirth operates within a complex context, where social, cultural, and economic factors interact with each other. At the Babirik Community Health Center (Puskesmas Babirik), community service partners face a number of challenges. One of the main issues is the limited human resources, with an insufficient number of medical personnel and volunteers to reach all pregnant women in the area. Ineffective communication between the health center and the community has led to low awareness and participation of pregnant women in existing programs.Based on these challenges, a solution was developed by introducing the Community Movement to Assist Childbirth at Puskesmas Babirik, abbreviated as Germas Tulin. The Germas Tulin program at Puskesmas Babirik has shown a positive impact on community service, especially in supporting childbirth. Through various initiatives, the community actively participates in providing services and support needed during the delivery process. Germas Tulin plays a vital role in creating a safer and more supportive environment for pregnant women, as well as contributing to the improvement of healthcare service quality in the area.